Analysis of Non Perfroming Loans in Indonesia: A Perspective of Market Discipline. - SEPTO HADI WIBOWO (Jurnal Ilmiah Mahasiswa FEB, 2018)
The  purpose  of  this  research  was  to  analyze  the  effect  of  bank  specific variables, including Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Asset (ROA), Return on Equity (ROE), and Loan Loss Provision (LLP), and  market  discipline  variables,  namely  Interbank  Deposit  Ratio  (IDR), Subordinated  Debt  (SND),  and  Information  Disclosure  Index  (ID)  on  Non- Performing Loan (NPL) Ratio. The data used in this study was annual data from 2006  to  2017  (12  years)  taken  from  BUKU  4  Conventional  Commercial  Banks annual  report.  This  study  used  multiple  linear  regression  analysis  and  Ordinary Least Square as the estimator with the help of a computer program, Stata version 14.2, as the main software to process the research data.  The  results  showed  that  together  (simultaneously)  the  independent variables (CAR, LDR, ROA, ROE, LLP, IDR, and SND) significantly affected the change  in  the  ratio  of  Non-Performing  Loan  (NPL).  While  partially,  all  of  CAR, LDR,  ROA,  and  ROE  had  significant  effect  on  NPL.  CAR  and  ROE  had significant  and  positive  effect,  while  LDR  and  ROA  had  significant  and negative effect  on  NPL.  The  other  3  variables,  including  LLP,  IDR,  and  SND,  have  non- significant  effect  on  NPL.  The  result  indicated  that  LLP  and  IDR  had  non- significant and negative effect, while SND had non-significant and positive effect on NPL. In addition, Information Disclosure Index (DI) variable was not included in the multiple linear regression model because the finding of this study showed that  all  BUKU  4  Banks  got  a  perfect  score  for  their  disclosure  index  each  year troughout 2006 to 2017 period, therefore the analysis for this variable was being done  descriptively.  In  other  words,  it  can  be  concluded  that  all  BUKU  4 Conventional  Commercial  Banks  already  disclose  every  information  required  in the  disclosure  index,  therefore,  the  DI  variable  can’t  be  used  as  a  parameter  to analyze the effect of market discipline variables on NPL.Keyword: NPL, CAR, ROA, SND, IDR